A censura do obsceno - Fernando Caetano Rocha Junior (2024)
The censorship of the obscene establishes a contemporary reflection on an ancient question still unanswered: the question of the limits of Free Speech. The attempt to advance the discussion about the desire and power to censor speeches considered offensive always seems to come up against polarized arguments full of prejudices and taboos that are amplified when we talk about sexuality, eroticity and nudity. Are there general criteria for distinguishing between erotic art and pornography? Could this distinction lead to the censorship of speech considered obscene? These questions have divided theorists of the most varied political and ideological inclinations. On the one hand, it seems mandatory that democracies guarantee freedom of expression as a way of legitimizing the exercise of power through Law, on the other hand, these same democracies have organized themselves in a way that rejects absolutism and liberality. Based on these variables, it seems socially desirable to seek answers, or at least advance the discussion about censorship, the obscene and the censorship of the obscene.